2014
DOI: 10.3109/02770903.2013.876431
|View full text |Cite
|
Sign up to set email alerts
|

Association of caregiver health beliefs and parenting stress with medication adherence in preschoolers with asthma

Abstract: Because the findings for parenting stress are not consistent with that of the literature on school-aged children with asthma, our results may suggest that preschool children are a unique developmental group. A review of endorsed health beliefs also highlights strengths and concerns for caregivers of these very young children. Overall, our study findings underscore the importance of caregivers' health-related beliefs in promoting adherence to ICS in young children with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 23 publications
0
26
0
4
Order By: Relevance
“…One study linked greater parental distress with better adherence, and two others found a negative association between caregiver depressive symptoms and adherence . Three studies found no relationship between caregiver psychological functioning and adherence …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study linked greater parental distress with better adherence, and two others found a negative association between caregiver depressive symptoms and adherence . Three studies found no relationship between caregiver psychological functioning and adherence …”
Section: Resultsmentioning
confidence: 99%
“…Research examining non‐modifiable individual influences has resulted in mixed findings. Related to youth age and medication adherence, there is some evidence indicating that older youth are less adherent to medication while other studies found a null association between youth age and adherence . While a number of studies have found no gender differences in adherence, others have found that females are less likely to have difficulties with adherence .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with other studies that have investigated the impact of caregivers on adherence. A recent study found that parents with negative health beliefs were significantly associated with poorer adherence to inhaled corticosteroid therapy for their children . In an older demographic, Foebel et al .…”
Section: Discussionmentioning
confidence: 99%
“…При этом некоторые родители открыто «сопротивляются» ежедневному приему препа-ратов ребенком, аргументируя это тем, что незачем «пичкать» лекарствами, если ребенок и так хорошо себя чувствует [34]. Такая мотивация может быть подкреплена и стероидофобией -опасением развития нежелатель-ных побочных эффектов у пациентов, которым назначены ИГКС [35,36].…”
Section: приверженность лечениюunclassified